Participatory Training on MSMEs - Warsani Purnama Sari; Ahmad Prayudi; Dhian Rosalina; Nina Siti Salmaniah Siregar (Journal of Innovation in Business and Economics, 2025)
This study examines the effect of participatory training and human resource (HR) competence on the performance of micro, small, and medium enterprises (MSMEs) operating in the Tangkahan ecotourism area, North Sumatra. Using survey data from 88 respondents across three tourist villages, this research employs multiple linear regression with a moderation approach to analyze the direct and moderating effects of training participation—measured by training planning participation, training relevance, and follow-up support—on the relationship between HR competence and MSME performance. The results show that HR competence has a positive and significant effect on MSME performance, confirming the importance of skills, adaptability, and experience in achieving business success. Conversely, training planning participation and training relevance show significant negative effects, indicating that inadequate involvement of MSMEs in designing training and a mismatch between training content and real business needs can hamper performance. Follow-up support was found to have no significant effect. Furthermore, the moderation analysis reveals that the dimensions of training participation do not significantly moderate the relationship between HR competence and MSME performance. These findings suggest that HR competence plays a more fundamental and independent role than participatory aspects of training, and highlight the need for training programs to be more contextually relevant, participatory, and aligned with the real needs of MSME actors to effectively improve business outcomes.